After the forest [large type] - Woods, Kell (Thorndike Press large print high octane., 2024)
"After the Forest is a dark and enchanting fantasy debut from Kell Woods that explores the repercussions of a childhood filled with magic and a young woman contending with the truth of "happily ever after." Ginger. Honey. Cinnamon. Flour. Twenty years after the witch in the gingerbread house, Greta and Hans are struggling to get by. Their mother and stepmother are long dead, Hans is deeply in debt from gambling, and the countryside lies in ruin, its people starving in the aftermath of a brutal war. Greta has a secret, though: the witch's grimoire, secreted away and whispering in Greta's ear for the past two decades, and the recipe inside that makes the best gingerbread you've ever tasted. As long as she can bake, Greta can keep her small family afloat. But in a village full of superstition, Greta and her mysteriously addictive gingerbread, not to mention the rumors about her childhood misadventures, is a source of gossip and suspicion. And now, dark magic is returning to the woods and Greta's magic--magic she is still trying to understand--may be the only thing that can save her. If it doesn't kill her first"--